A carbon metering method for distribution networks considering harmonic influences - Yu, Jicheng; Chen, Hao; Wang, Zhen; Zhou, Feng; Yin, Xiaodong; Yue , Changxi (Frontiers in Energy Research, 2023)
Harmonic brought about by the large number of impulsive and non-linear loads connected to the grid has led to new challenges in regional carbon emissions management. The existence of harmonics increases the consumption of power equipment, and the transformation of signal form makes the accuracy of carbon measurement questioned, which damages the fairness, and is not conducive to a carbon trading market construction and the purpose of precise carbon verification. This paper proposes that the harmonic level of each node is monitored during the carbon metering of the distribution network, the carbon metering results are corrected based on the correction amount of the harmonic carbon. Harmonic separation and electric carbon conversion of the current-containing harmonic source are conducted on the IEEE33 node. The results show that harmonic carbon does exist. Carbon metering results are affected when the power quality is distorted seriously, which is not conducive to establish a carbon metering trading market.